Prenatal development of the human entorhinal cortex. Issue 15 (23rd May 2022) - Šimić, Goran; Krsnik, Željka; Knezović, Vinka; Kelović, Zlatko; Mathiasen, Mathias Lysholt; Junaković, Alisa; Radoš, Milan; Mulc, Damir; Španić, Ena; Quattrocolo, Giulia; Hall, Vanessa Jane; Zaborszky, Laszlo; et al.
Abstract: Little is known about the development of the human entorhinal cortex (EC), a major hub in a widespread network for learning and memory, spatial navigation, high‐order processing of object information, multimodal integration, attention and awareness, emotion, motivation, and perception of time. We analyzed a series of 20 fetal and two adult human brains using Nissl stain, acetylcholinesterase (AChE) histochemistry, and immunocytochemistry for myelin basic protein (MBP), neuronal nuclei antigen (NeuN), a pan‐axonal neurofilament marker, and synaptophysin, as well as postmortem 3T MRI. In comparison with other parts of the cerebral cortex, the cytoarchitectural differentiation of the EC begins remarkably early, in the 10th week of gestation (w.g.). The differentiation occurs in a superficial magnocellular layer in the deep part of the marginal zone, accompanied by cortical plate (CP) condensation and multilayering of the deep part of CP. These processes last until the 13–14th w.g. At 14 w.g., the superficial lamina dissecans (LD) is visible, which divides the CP into the lamina principalis externa (LPE) and interna (LPI). Simultaneously, the rostral LPE separates into vertical cell‐dense islands, whereas in the LPI, the deep LD emerges as a clear acellular layer. In the 16th w.g., the LPE remodels into vertical cell‐dense and cell‐sparse zones with a caudorostral gradient. At 20 w.g., NeuN immunoreactivity is most pronounced in the islands of layer II cells, whereas migration and differentiation inside‐out gradients are seen simultaneously in both the upper (LPE) and the lower (LPI) pyramidal layers. At this stage, the EC adopts for the first time an adult‐like cytoarchitectural organization, the superficial LD becomes discernible by 3T MRI, MBP‐expressing oligodendrocytes first appear in the fimbria and the perforant path (PP) penetrates the subiculum to reach its molecular layer and travels along through the Cornu Ammonis fields to reach the suprapyramidal blade of the dentate gyrus, whereas the entorhinal‐dentate branch perforates the hippocampal sulcus about 2–3 weeks later. The first AChE reactivity appears as longitudinal stripes at 23 w.g. in layers I and II of the rostrolateral EC and then also as AChE‐positive in‐growing fibers in islands of superficial layer III and layer II neurons. At 40 w.g., myelination of the PP starts as patchy MBP‐immunoreactive oligodendrocytes and their processes. Our results refute the possibility of an inside‐out pattern of the EC development and support the key role of layer II prospective stellate cells in the EC lamination. As the early cytoarchitectural differentiation of the EC is paralleled by the neurochemical development, these developmental milestones in EC structure and connectivity have implications for understanding its normal function, including its puzzling modular organization and potential contribution to consciousness content (awareness), as well as for its insufficiently explored deficits in developmental, psychiatric, and degenerative brain disorders. Abstract : We describe the major events in the prenatal development of the human entorhinal cortex (EC) by analyzing 20 fetal brains aged 9–40 weeks of gestation (w.g.). At 20 w.g., NeuN immunoreactivity is most pronounced in the EC layer II, while migration and differentiation inside‐out gradients are seen simultaneously in both LPE and LPI as well as in layer II. At this stage, upon separation from the angular bundle (ab) the temporoammonic branch of the perforant path (PPtab) reaches the suprapyramidal blade of the dentate gyrus (arrows). PPtab are the perforant path fibers of its main (temporoammonic) branch, whereas PPcross are the crossed perforant path fibers from the opposite hemisphere; AP is the alvear path. Our results support the key role of layer II prospective stellate cells in EC lamination.